From The Begriffsschrift To "Über Sinn Und Bedeutung": Frege As Epistemologist And Ontologist - Max Rosenkrantz (Manuscrito)
ABSTRACT Frege presents the eponymous distinction of "Über Sinn und Bedeutung" (USB) as a correction to the theory of identity he held in the Begriffsschrift.1 His retrospective assessment has prompted different reactions from commentators. Many have simply taken him at his word.2 Others, who have lingered over the relevant texts, have encountered a difficulty: in the Begriffsschrift Frege appears to raise the same problem with which he begins USB and to respond to it in words that are strikingly similar to those found in the later work.3 Thus, a number of important scholars have been led to argue that Frege misrepresents his earlier view: contrary to what he says in USB, the Begriffsschrift already contains the distinction between Sinn and Bedeutung.4 Despite their obvious differences, the logic of both interpretations requires that the two works be responsive to the same problem. In this paper I challenge that fundamental premise.5 If I might be allowed to express my thesis tersely but suggestively: the problem of the Begriffsschrift is epistemological; that of USB, ontological.6 The two problems and Frege's solutions to them shall be explained in what follows.